Effort-reward imbalance among students at German universities: associations with self-rated health and mental health - Hilger-Kolb, Jennifer; Diehl, Katharina; Herr, Raphael M.; Loerbroks, Adrian (International Archives of Occupational and Environmental Health, 2018)
Purpose: Although psychosocial stress has been associated with adverse health parameters, little is known about this topic among the variety of university students. We thus examined associations of psychosocial stress due to academic education with self-rated health, and symptoms of depression and anxiety among students from various study disciplines. Methods: We used data from the Nutrition and Physical Activity (NuPhA) Study, a cross-sectional online survey among students enrolled across German universities (n = 698). Academic stress was assessed by a newly developed and validated student version of the Effort–Reward Imbalance (ERI-Student) Questionnaire. Depressive and anxiety symptoms were measured by applying the Patient Health Questionnaire-4 (PHQ-4) and using validated cut-offs. Results: Separate multivariate logistic regression analyses run for the different ERI components, the ERI-ratio revealed that high effort, low reward, high over-commitment, and a high ERI-ratio were associated with poor self-rated health, and depressive and anxiety symptoms (odds ratios ≥ 2.43). Separate analyses for medical students and non-medical students largely confirmed these findings for both groups. Associations between all ERI components, the ERI ratio, and both mental health measures were, however, more pronounced among medical students. Conclusions: We were able to show consistent associations between the ERI-Student Questionnaire and self-rated health and mental health across students from different study disciplines. Further research on associations between academic stress and health parameters is necessary to develop effective strategies that prevent students from adverse health outcomes during their academic education.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Effort-reward imbalance; Mental health; Psychosocial stress; Self-rated health; University students